Analysis of Experience of Using Small UAVs in the Battlefield: Training Enhancement Perspectives - Reznik, Оleh; Kustynsky, Oleh; Horpynych, Petro; Aleksandrovych, Volodymyr (Educological discourse, 2024)
The article analyzes the experience of the State Border Guard Service units in fighting russian occupying forces inflicting the fire damage with the help of small UAVs and describes the ways to use the acquired experience to develop a training course for the border guard UAV operators. The authors state that nowadays, in the conditions of the of full-scale invasion to Ukraine, active using of unmanned aerial vehicles (hereinafter – UAVs) proved their ability to perform combat tasks, making them one of the new and effective types of weapons in modern military conflicts. It is impossible to imagine a contemporary army without UAVs, as today they perform multiple roles: adjusting artillery fire, pointing and tracking targets, transmitting intelligence information to the headquarters, delivering fire strikes, and most importantly – they can help save the lives of soldiers. Analysis of a year and a half term of full-scale invasion of Ukraine showed that the use of UAVs is several times more effective than the use of traditional types of weapons. In the first days of the war, a huge number of the russian battalion tactical groups (hereinafter – BTGs) were concentrated on the borders of Ukraine, and that significantly outweighed the forces and means of military formations of Ukraine. Analysis also proves that the main striking force during the offensive, according to the governing documents, were armored fighting vehicles, infantry fighting vehicles, amphibious assault vehicles, armored personnel carriers. And it was possible to stop enemy columns only with the help of artillery, aviation, and anti-tank missile systems. Therefore, in modern conditions, it is necessary to create fire damage to enemy armored vehicle groups with the help of attack UAVs of the border guard units. The article considers the effectiveness of such a unit, taking into account the tasks, organizational structure, forces and means necessary to respond to modern challenges and threats on the state border. The authors used the acquired experience of the Border Guard units to develop a training course for the UAV operators of the border guard units. The developers of the course took into account the combat experience and the best European practices in UAV operators training. The learning strategy of the course is based on a student-centred learning approach. It is designed to provide learners with theoretical knowledge and practical skills on the operators of the UAV crews deployed in border surveillance and combat operations. The course is divided in three phases: Independent Learning Phase (online), Contact Learning Phase (offline) and Experiential Learning Phase (at the border guard units).